Thermal Properties of Epoxy Resins and Phenol Formaldehyde Component with Differential on the Mixing Ratios and Reinforced by Nanoparticles - Mustafa Ahmed Rajab (Journal of Global Pharma Technology, 2016)
The research aims to study the mechanical properties (tensile strength, hardness, Impact) and thermal properties of epoxy resin and phenol formaldehyde by varying the mixing and strengthening ratios of the nanoparticles. First: (the effect of different mixing ratios between epoxy resins and phenol formaldehyde), and secondly: (nanoparticles containing both magnesium oxide and zirconium oxide) on both mechanical and thermal properties.Keywords: Mechanical and Thermal Properties, Composite Material, Mixing ratios.